Types of concrete test on construction (Perumahan Kastam Larkin) / Khairul Nizam Hussain - Hussain, Khairul Nizam (2015)
There are many type of concrete I have done while I’m in Gerbang Nusajaya team in Perumahan Kastam Larkin such as solve problem in the building when the problem occur. Throughout my as trainees in the Perumahan Kastam Larkin I got a lot of new thing that I have, one of them working concrete work carried out and monitoring concrete work. During the four months of practical training at Gerbang Nusajaya Sdn. Bhd., I have learned how theory and practical can be combined together in useful ways and how remarkable and enjoyable practical training could be. While deadlines and skills are highly demanded, creativity is not limited and true innovation occurs throughout my practical training at Perumahan Kastam Larkin As a result, I gained more knowledge and learned new things and most importantly I experienced the real working environment all by myself. In term of relationship, I was lucky enough to work with a group of enthusiastic and communicative people, who for whatever reason willing to share their knowledge and experience of what they are doing. Besides, the atmosphere at Perumahan Kastam Larkin is unique and hope that it will stays that way.